Role of the oxygen uptake efficiency slope in evaluating exercise tolerance. Issue 1 (1st July 1999) - Baba, Reizo; Nagashima, Masami; Nagano, Yoshiko; Ikoma, Masanobu; Nishibata, Kenji
Abstract : OBJECTIVE: To investigate the interprotocol agreement of oxygen uptake efficiency slope (OUES). METHODS: 16 Japanese children and adolescents (10 boys and six girls) underwent two sessions of maximal exercise testing according to the following two treadmill protocols: the standard Bruce protocol and the rapidly increasing staged (RIS) protocol. Maximal oxygen uptake (VO2 max), the ventilatory anaerobic threshold (VAT), and the OUES were obtained from the gas analysis data. Agreement between the protocols was tested by means of the Bland-Altman method. RESULTS: Interprotocol agreement was excellent for the OUES (limit of agreement, −18% to 17% of the mean value), slightly less good for VO2 max (limit of agreement, −20% to 24% of the mean value), and poor for the VAT (limit of agreement, −31% to 31% of the mean value). CONCLUSION: These results confirm the clinical usefulness of the OUES as a measure of evaluating exercise tolerance in the paediatric population.